2017
DOI: 10.1371/journal.pone.0181186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of versatile derivatives from a GFP-like protein in the marine copepod Chiridius poppei

Abstract: Fluorescent proteins are now indispensable tools in molecular research. They have also been adapted for a wide variety of uses in cases involving creative applications, including textiles, aquarium fish, and ornamental plants. Our colleagues have previously cloned a yellow GFP-like protein derived from the marine copepod Chiridius poppei (YGFP), and moreover, succeeded in generating transgenic flowers with clearly visible fluorescence, without the need for high-sensitivity imaging equipment. However, due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Using our novel fluorescent genes, we have succeeded in generating P. hybrida plants exhibiting brilliant green fluorescence, which could be easily visualized at whole plant level without using any high sensitive imaging equipment. Because the excitation maximum of eYGFPuv is within the UV-A region (400 nm) 23 , the fluorescence of these transgenic plants was observed without any emission filter, which constitutes a crucial progress from previously reported fluorescent flowers 21 . Notably, we could obtain bright fluorescent images under unexceptional image acquisition conditions (≤2 s exposure; Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Using our novel fluorescent genes, we have succeeded in generating P. hybrida plants exhibiting brilliant green fluorescence, which could be easily visualized at whole plant level without using any high sensitive imaging equipment. Because the excitation maximum of eYGFPuv is within the UV-A region (400 nm) 23 , the fluorescence of these transgenic plants was observed without any emission filter, which constitutes a crucial progress from previously reported fluorescent flowers 21 . Notably, we could obtain bright fluorescent images under unexceptional image acquisition conditions (≤2 s exposure; Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 78%
“…1b ) 23 . For reference, the sequences, structure, and detailed fluorescence properties of each fluorescent protein were briefly reproduced in supplementary information (Supplementary Figure S1 and Supplementary Table S1 ) 23 . We first examined the intracellular localizations of eYGFPuv and eYGFP stably expressed in tobacco BY-2 cells and confirmed that the fluorescence of these FPs, as well as that of intact CpYGFP, was mainly observed in the cytoplasm with no preferential localization to the nucleus or vacuole (Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations